Catalytic Dry-reforming of Methane Process with Co,Ni,Pd/Ca-La-O Mixed Oxides - Al-Doghachi, Faris Jasim; Al-Najar, Ali M. A.; Safa-Gamal, M.; Taufiq-Yap, Yun Hin (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
A surfactant-assisted co-precipitation method was used to prepare the catalysts Co,Ni,Pd/CaO, Co,Ni,Pd/Ca0.97La3+0.03O, Co,Ni,Pd/Ca0.93La3+0.07O, and Co,Ni,Pd/Ca0.85La3+0.15O (1% each of Co, Ni, and Pd). La2O3 doping effect on the activity and stability of Co,Ni,Pd/CaO catalysts was investigated in dry reforming of methane. Catalysts were characterized by several techniques (X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET), X-ray Fluorescence (XRF), Fourier Transform Infra Red (FTIR), Temperature Programmed Desorption H2 (H2-TPR), Transmission electron microscopes (TEM), and Temperature Gravimetric Analysis (TGA)) and were tested in a fixed-bed reactor at 900 °C and (Gas Hourly Specific Velocity (GHSV) = 15000 mL.gcat−1.h−1, atmospheric pressure).  Adding La2O3 had little effect on the morphology of the Co,Ni,Pd/CaO catalyst. However, it played a crucial role in enhancing the catalyst’s reducibility and CO2 adsorption at high temperatures, as indicated by the activity and stability of the Co,Ni,Pd/CaO catalyst. The carbon deposition on utilized catalysts after 5 hours at 900 °C was examined using TEM and thermal gravimetric analysis (TGA) techniques. Compared to Co,Ni,Pd/CaO catalysts across the entire temperature range, the tri-metallic Co,Ni,Pd/Ca0.85La3+0.15O catalyst with a lanthanum promoter demonstrated a greater conversion of CH4 (84%) and CO2 (92 %) at a 1:1 CH4:CO2 ratio. The selectivity of H2/CO reduced in the following order: Co,Ni,Pd/Ca0.85La3+0.15O > Co,Ni,Pd/Ca0.93La3+0.07O > Co,Ni,Pd/Ca0.97La3+0.03O > Co,Ni,Pd/CaO. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).